Diabetes mellitus : enquiry into its medical aspects and bioengineering of its monitoring and regulation - Acharya, U. Rajendra (2013)
Diabetes mellitus (DM) or hyperglycemia (in a more generalized term, high blood sugar) is a metabolic disorder that is now highly prevalent in the world population. Most of the food that people consume is converted into glucose, which enters the bloodstream following absorption–assimilation mechanisms. As a natural process, cells in our body utilize glucose for growth and energy. The glucose balance is maintained by a hormone called insulin that is secreted by the beta cells of pancreas. Hypotheses at the backdrop of DM occurrence are either (i) enough insulin is not produced and secreted resulting in increased level of glucose in blood, or (ii) insulin is insensitive to glucose, or (iii) insulin is non-targeted etc. If DM remains uncontrolled over time, it leads to serious damage to many of the body's systems, especially the nerves and blood vessels. This paper develops an enquiry into diabetes from many angles: (i) Diabetes as a disorder, its complications, causes, diagnostic tests, and treatment; (ii) Analysis of retinal and plantar images to characterize diabetes complications; (iii) How analysis of heart rate variability signals can depict diabetes; (iv) Biomedical engineering of the glucose–insulin regulatory system, and its employment in the modeling of the oral glucose tolerance test data, to detect diabetes as well as persons at risk of being diabetic; (v) Application of the glucose–insulin regulatory system to formulate an insulin delivery system for controlling blood sugar.